Effectiveness and safety of sofosbuvir‐based regimens plus an NS5A inhibitor for patients with HCV genotype 3 infection and cirrhosis. Results of a multicenter real‐life cohort. Issue 4 (9th December 2016) - Alonso, S.; Riveiro‐Barciela, M.; Fernandez, I.; Rincón, D.; Real, Y.; Llerena, S.; Gea, F.; Olveira, A.; Fernandez‐Carrillo, C.; Polo, B.; Carrión, J. A.; Gómez, A.; et al.
Summary: Patients with HCV genotype 3 (GT3) infection and cirrhosis are currently the most difficult to cure. We report our experience with sofosbuvir+daclatasvir (SOF+DCV) or sofosbuvir/ledipasvir (SOF/LDV), with or without ribavirin (RBV) in clinical practice in this population. This was a multicenter observational study including cirrhotic patients infected by HCV GT3, treated with sofosbuvir plus an NS5A inhibitor (May 2014‐October 2015). In total, 208 patients were included: 98 (47%) treatment‐experienced, 42 (20%) decompensated and 55 (27%) MELD score >10. In 131 (63%), treatment was SOF+DCV and in 77 (37%), SOF/LDV. Overall, 86% received RBV. RBV addition and extension to 24 weeks was higher in the SOF/LDV group (95% vs 80%, P=.002 and 83% vs 72%, P=.044, respectively). A higher percentage of decompensated patients were treated with DCV than LDV (25% vs 12%, P=.013). Overall, SVR12 was 93.8% (195/208): 94% with SOF+DCV and 93.5% with SOF/LDV. SVR12 was achieved in 90.5% of decompensated patients. Eleven treatment failures: 10 relapses and one breakthrough. RBV addition did not improve SVR (RR: 1.08; P=.919). The single factor associated with failure to achieve SVR was platelet count <75×10E9/mL (RR: 3.50, P=.019). In patients with MELD <10, type of NS5A inhibitor did not impact on SVR12 (94% vs 97%; adjusted RR: 0.49). Thirteen patients (6.3%) had serious adverse events, including three deaths (1.4%) and one therapy discontinuation (0.5%), higher in decompensated patients (16.7% vs 3.6%, P<.006). In patients with GT3 infection and cirrhosis, SVR12 rates were high with both SOF+DCV and SOF/LDV, with few serious adverse events.